Pengaruh Komunikasi Word Of Mouth dan Place Terhadap Keputusan Pembelian pada Usaha Susu Kambing Etawa Mulia Jaya Di Desa Melati II Kecamatan Perbaungan - Pristiwati Pristiwati; Muhammad Hilman Fikri (Universitas Nusantara PGRI Kediri, 2021)
This study aims to determine and test whether Word Of Mouth and Place Communication affect the Purchase Decision on the Etawa Mulia Jaya Goat Milk business in Melati II Village, Perbaungan District. The sample used in this study were consumers who were consuming Etawa Mulia Jaya Goat's Milk products with a total of 87 consumers who were taken for 3 months. The results of the study using the t-test (partial) showed that Word Of Mouth Communication had a significant effect on Purchase Decisions with a tcount value of 4.051 > ttable 1.988 and a significant level of 0.000 <0.05 and that Place had a significant effect on Purchase Decisions with a tcount value of 3.455. > ttable 1.988 with a significant level of 0.001 <0.05. The results of the study using the F (simultaneous) test showed that Word Of Mouth and Place Communication simultaneously had a significant effect on Purchase Decisions with an Fcount of 42.856 > Ftable 3.11 with a significant level of 0.000 <0.05. Based on calculations using the coefficient of determination, the Adjusted R Square value of 0.493 shows that around 49.3% of the Purchase Decision variables can be explained by the Word Of Mouth and Place Communication variables.